WHO Functioning and Disability Disaggregation (FDD11) tool: a reliable approach for disaggregating data by disability - Lindsay Lee; Kaloyan Kamenov; Carolina Fellinghauer; Carla Sabariego; Somnath Chatterji; Alarcos Cieza (BMC, 2022)
Abstract Background There is a global scarcity of good quality disability data, which has contributed to a lack of political will to address the challenges that persons with disabilities face. The current paper proposes a way forward to overcome this gap by demonstrating the psychometric properties of the World Health Organization Functioning and Disability Disaggregation Tool (FDD11) - a brief disability disaggregation instrument that countries can use. Results The study demonstrated that FDD11 is a valid and reliable tool. Unidimensionality of the scale produced by each calibration was supported by the factor analysis performed. The analysis indicated good fit of the items, and targeting of the items was deemed to be sufficient. The person separation index was 0.82, indicating good reliability of the final scale. Conclusion FDD11 provides a good opportunity to researchers and governments to capture good quality disability data and to disaggregate existing data by disability. The tool can facilitate low- and middle-income countries in their efforts to develop evidenced-based policies to address any barriers faced by persons with disabilities, to monitor the implementation of the Convention on the Rights of Persons with Disabilities and the Sustainable Development Goals, and to take stock of the challenges that still remain.